A graphene superficial layer for the advanced electroforming process. Issue 25 (7th March 2016) - Rho, Hokyun; Park, Mina; Lee, Seungmin; Bae, Sukang; Kim, Tae-Wook; Ha, Jun-Seok; Lee, Sang Hyun
Abstract : The innovative electroforming process facilitate the progress of electronic devices, including microelectronic, flexible electronic/optoelectronic, and sensor applications. Abstract : Advances in electroplating technology facilitate the progress of modern electronic devices, including computers, microprocessors and other microelectronic devices. Metal layers with high electrical and thermal conductivities are essential for high speed and high power devices. In this paper, we report an effective route to fabricate free-standing metal films using graphene as a superficial layer in the electroforming process. Chemical vapor deposition (CVD) graphene grown on a Cu foil was used as a template, which provides high electrical conductivity and low adhesive force with the template, thus enabling an effective electroforming process. The required force for delamination of the electroplated Cu layer from graphene is more than one order smaller than the force required for removing graphene from the Cu foil. We also demonstrated that the electroformed free-standing Cu thin films could be utilized for patterning microstructures and incorporated onto a flexible substrate for LEDs. This innovative process could be beneficial for the advancement of flexible electronics and optoelectronics, which require a wide range of mechanical and physical properties.